2016
DOI: 10.1007/s00270-016-1479-y
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Coated Balloons for the Treatment of Dysfunctional Dialysis Access. Results from a Single-Center, Retrospective Analysis

Abstract: In this retrospective analysis, Lutonix PCB proved to be safe and effective in treating restenosis in dysfunctional dialysis access with results comparable to the literature available. Larger studies are needed to prove abovementioned results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…These findings are similar to those described by Patané et al (20), Kitrou et al (21), Lai et al (22), and Katsanos et al (23). However, in the Katsanos et al (23) prospective study of 40 patients and in the Kitrou et al (21) retrospective study of 39 patients, the cohorts had a high proportion of AVGs (n = 26 and n = 19, respectively). In the Lai et al (22) observational study and in the Patane et al (20) retrospective study, the lesions treated were only within the juxta-anastomotic segment of radiocephalic AVFs.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are similar to those described by Patané et al (20), Kitrou et al (21), Lai et al (22), and Katsanos et al (23). However, in the Katsanos et al (23) prospective study of 40 patients and in the Kitrou et al (21) retrospective study of 39 patients, the cohorts had a high proportion of AVGs (n = 26 and n = 19, respectively). In the Lai et al (22) observational study and in the Patane et al (20) retrospective study, the lesions treated were only within the juxta-anastomotic segment of radiocephalic AVFs.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, CVS was not treated in either of these studies, as balloons were available in diameters only as large as 7 mm, making them unsuitable for CVS treatment. The same group of investigators (18) recently published a retrospective analysis of the use of another PCB for the treatment of dysfunctional dialysis access. Data presented were comparable with those from the previous randomized studies.…”
Section: Discussionmentioning
confidence: 96%
“…Paclitaxel-coated balloons (PCBs) have been tested for their safety and efficacy in the treatment of dysfunctional dialysis access in a few randomized studies and retrospective analysis of cases, with encouraging results so far (14)(15)(16)(17)(18). In two randomized controlled trials that used PCBs in arteriovenous fistulae (AVFs) and the venous outflow of arteriovenous grafts (AVGs) (14,15), the use of PCBs demonstrated significantly better results than conventional angioplasty.…”
mentioning
confidence: 96%
“…In the three studies that included patients with AVG, the number of patients with AVG was small. Moreover, patency rate of the AVG post‐treatment PCB was not specifically reported in these studies. Our study included a substantial proportion of AVG and we showed the beneficial effects of PCB on AVG patency following intervention compared to plain balloon at 3 and 6 months.…”
Section: Discussionmentioning
confidence: 99%